The use of fish silage to increase feed efficiency and growth of grouper (Epinephelus coioides) in floating net cages - Agus Putra AS; Muhammad Amin; Baihaqi Baihaqi; Muhammad Hatta; Eva Ayuzar (Depik, 2021)
This study aimed to investigate the efficiency of fish silage mixed in compounded diets on growth and survival rate of grouper (Epinephelus coioides). Grouper (2,34±0,24 cm, and 4,17±1,82 g) were divided into four groups and cultivated in 1x1x1,5 m floating net cages. Each group fed with compounded diets containing 0, 1, 3 and 5 g/kg fish silage diet twice daily. Fish were sampled for growth performances and feed efficiency at 14 days interval for 10 weeks. Results indicated that compounded diets at 1 and 3 g/kg silage affected the growth rate. Total length, specific growth rate and weight gain significantly increased in fish received 1 and 3 g/kg silage diets. The feed intake seen to be highest in groups administered 3 g/kg silage, whereas the best feed conversion ratio was found in fish fed 1 g/kg silage. Thus, this study indicated that using fish silage in compounded diets may affect feed efficiency and growth performances of grouper juveniles.Keywords:Artificial dietFeedingFish silageGrouperNet cages